(untitled) (Actualizaciones en Sida e Infectología, 2022)
In recent years, the emergence of daptomycin-resistant enterococcus strains is a growing clinical and epidemiological topic of concern. We report the case of a 50-year-old patient with an antecedent of rheumatoid arthritis and chronic immunosuppression hospitalized in the context of COVID-19 pneumonia with bacterial co-infection and septic shock in which a three different moments an isolate of a vancomycin-resistant enterococcus faecium (VRE) VAN A and B that presented therapeutic failure with daptomycin was documented after clinical deterioration and persistence of positive blood cultures. Linezolid was initiated, with clinical recovery and negativization of blood cultures following the change in antibiotic treatment. This case is reported in order to expose the ever growing concern of daptomycin-resistant enterococcus strains in order to prevent therapeutic failure, make early identification and get to know the local epidemiological status.